CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND INDONESIAN PRONOUNS THROUGH SEMANTIC COMPONENTS - Ruddamayanti Ruddamayanti (Universitas PGRI Palembang, 2020)
The purposes of this study are to discover the similarities and differences between English and Indonesian pronouns based on semantic components, to predict the possible difficulties faced by Indonesian students in learning English pronouns, and to find out the implications for language teaching. In this study, the writer used the descriptivequalitative method. In collecting and validating the data, the writer applied the triangulation technique. It used documentation, observation, and interview techniques. Based on the findings, it was found that they were eight similarities and three differences between English and Indonesian pronouns through semantic components; three possible difficulties problems faced by Indonesian students in learning English pronouns; and two implications for language teaching.